Promising Anti-Biofilm Agents and Phagocytes Enhancers for the Treatment of Candida albicans Biofilm–Associated Infections - Tartor, Yasmine H.; Elmowalid, Gamal A.; Hassan, Mohamed N.; Shaker, Asmaa; Ashour, Dalia F.; Saber, Taisir (Frontiers in Cellular and Infection Microbiology, 2022)
Little is known about the interactions among phagocytes and antifungal agents and the antifungal immunomodulatory activities on Candida species biofilms. Here, inhibition of C. albicans biofilms and the interactions among biofilms and phagocytes alone or in combination with essential oils, biological, and chemical agents, or fluconazole were investigated. Biofilm formation by a panel of 28 C. albicans clinical isolates from hospitalized patients, birds, and cattle was tested. The anti-biofilm activities of cinnamon and clove oils, sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), and Enterococcus faecalis cell-free supernatant (CFS) in comparison with fluconazole were investigated using crystal violet and XTT reduction assays, expression of hypha-specific and hyphal regulator genes, and scanning electron microscopy (SEM) analysis. Of the tested C. albicans isolates, 15 of 28 (53.6%) were biofilm producers. Cinnamon followed by E. faecalis–CFS, SDS, and CTAB was the most effective inhibitors of planktonic C. albicans and biofilms. Fluconazole was an ineffective inhibitor of C. albicans biofilms. Sessile minimal inhibitory concentration (SMIC50) of cinnamon, SDS, CTAB, and E. faecalis–CFS downregulated the hypha-specific and regulator genes, albeit to various extents, when compared with untreated biofilms (P < 0.001). SEM analysis revealed disruption and deformity of three-dimensional structures in cinnamon oil–treated biofilms. C. albicans sessile cells within biofilm were less susceptible to phagocytosis than planktonic cells. The additive effects of phagocytes and the tested antifungals enabled phagocytes to engulf C. albicans cells rapidly in cinnamon, E. faecalis–CFS, or SDS-treated biofilms. No differences in anti-Candida or anti-biofilm eradication activities were detected among the tested isolates. Our findings reinforce the substantial anti-biofilm activity of cinnamon oil, SDS, and E. faecalis–CFS and provide new avenues for the development of novel anti-biofilm immunotherapies or antifungals that could be used prior to or during the management of cases with biofilm-associated infections.